ANALISIS KUALITAS INFORMASI AKUNTANSI SEBELUM dan SESUDAH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS PADA PERUSAHAAN MANUFAKTUR TBK - Halim, Lina; Shanti, Shanti (Jurnal Akuntansi Kontemporer, 2015)
IFRS adoption occurs evenly throughout most of the world, aiming to improve the quality of accounting information accompanied by uniformity of standards for financial statements. This study aims to examine the quality of accounting information in Indonesia from the period before the adoption of IFRS until after the adoption of IFRS. This empirical study uses the data of consolidated fi-nancial statements and stock price information on all manufacturing companies listed on the Indonesia Stock Exchange from 2005-2012. This study uses the relevance of value and earnings management as a proxy for the quality of accounting information. Value relevance is measured using the price model, while earnings management is measured using the Jones Model. Each proxy is meas-ured using appropriate metrics in previous studies. The results showed that after adopting IFRS, the relevance of the value of accounting information increased. Different results are demonstrated through the earnings management proxy, where earnings management practices improve after adopting IFRS. Improved earnings management is due to the transition from the basis of rules into principles, where a more flexible principle basis is able to provide a loophole for earnings management.